Antibacterial and Antioxidant Compounds from the Flower Extracts of Vernonia amygdalina - Abere Habtamu; Yadessa Melaku (Hindawi Limited, 2018)
Vernonia amygdalina is traditionally used in Ethiopia to treat various diseases. This prompted us to isolate bioactive compounds from the flowers of this plant. The CHCl3 extract after silica gel column chromatography has led to the isolation of two compounds identified as tricosane (1) and vernolide (2), while the acetone extract furnished isorhamnetin (3) and luteolin (4). The acetone extract and isorhamnetin significantly scavenged the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical by 91.6 and 94%, respectively. It was also shown that the acetone extract and isorhamnetin inhibited lipid peroxidation by 74 and 80%, respectively. The extracts and isolated compounds were also evaluated for their antibacterial activity with the CHCl3 extract and vernolide showing strong activity against S. aureus with an inhibition zone of 21 and 19 mm, respectively. On the other hand, the acetone extract and isorhamnetin were active against all bacterial pathogens tested. The work presented herein has demonstrated that vernolide and isorhamnetin had antibacterial activity. The antioxidant activity displayed by the flowers of V. amygdalina is accounted to the presence of isorhamnetin. Therefore, the biological activities displayed by the extracts and isolated compounds from this plant corroborate the traditional uses of this plant by the local people against various diseases.